Out-of-Market Agricultural Property Trading in Poland - Tomasz Klusek (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
In the category of land property, the Civil Code specifies agricultural property. Similarly to other real property, they can be traded in the form of transfer of the ownership title, which occurs on commercial terms or with such terms excluded. In this study, out-of-market transactions with agricultural property. On the basis of the available data, changes in the figures, structure and regional differentiation of such transactions were presented. Attention was also paid to why such changes occurred.